2004
DOI: 10.1051/apido:2004056
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coumaphos on queen rearing in the honey bee, Apis mellifera

Abstract: -Young honey bee larvae were transferred into the queen cups containing known concentrations (0 to 1000 mg/kg) of the organophosphate pesticide coumaphos. These larvae were placed in queenless colonies and examined ten days later to determine the rate of rejection or acceptance as indicated by a mature sealed queen cell. All queens failed to develop at 1000 mg/kg, and greater than 50% of the queen cells were rejected at the 100 mg/kg concentration. Additionally, queens that survived exposure to100 mg/kg coumap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(80 citation statements)
references
References 8 publications
2
72
1
3
Order By: Relevance
“…Queen problems may lead to weak colonies and thus high losses. In addition, queen problems can be an indication of colony problems (Collins and Pettis 2013;Pettis et al 2004;Tarpy et al 2012). Note that even though our survey shows an association between queen problems and colony losses, it does not imply a causal relationship.…”
Section: Discussioncontrasting
confidence: 59%
“…Queen problems may lead to weak colonies and thus high losses. In addition, queen problems can be an indication of colony problems (Collins and Pettis 2013;Pettis et al 2004;Tarpy et al 2012). Note that even though our survey shows an association between queen problems and colony losses, it does not imply a causal relationship.…”
Section: Discussioncontrasting
confidence: 59%
“…Biotic factors, such as differences in drone availability, density, and sperm loads among males, could also create significant variation among queens (Haberl and Tautz, 1999;Schluns et al, 2003). Management practices may also significantly affect the overall quality of queens across sources, as different genetic stocks (see Tarpy and Nielsen, 2002), chemical treatments (Haarmann et al, 2002;Pettis et al, 2004), and hive environments (Woyke, 1983;da Silva et al, 1995) are all significant factors in the reproductive biology of queens.…”
Section: Discussionmentioning
confidence: 99%
“…As no single explanation for the extensive colony losses has been identified, it is concluded that many biological and environmental stressors, acting alone or in combination, can lead to premature colony mortality (vanEngelsdorp et al 2009, Genersch 2010. Along with bee diseases, many problems in beekeeping are caused by chemicals used against honey bee pathogens, whose appliance is accompanied by side effects on bees and brood (Pettis et al 2004a, 2004b, Loucif-Ayad et al 2008, contamination of bee products (Bogdanov 2006) and health risk to beekeepers and bee product consumers (Stanimirovic et al 2005, Stevanovic et al 2008, Radakovic et al 2013. Therefore, it would be benefitial if some harmless naturalbased supplements could provide maintaining healthy and strong honey bee colonies and help in prevention of their mortality.…”
Section: Honey Bees Apis Mellifera L (Hymenopteramentioning
confidence: 99%